Identification of COL1A1 and COL1A2 as candidate prognostic factors in gastric cancer. Issue 1 (December 2016) - Li, Jun; Ding, Yuemin; Li, Aiqing
Abstract Background The role of type I collagen, composed of collagen type I alpha 1 (COL1A1) and collagen type I alpha 2 (COL1A2), has been studied in several cancers. However, the expression of COL1A1 and COL1A2 in malignant, premalignant, and normal gastric tissues and their clinical significances in gastric cancer have not been elucidated. Methods Real-time quantitative PCR was performed in 55 malignant, 27 premalignant, and 19 normal tissues to measure COL1A1 and COL1A2 messenger RNA (mRNA) expression, and the correlations between COL1A1 and COL1A2 expression and clinicopathological parameters and patients' survival rate were analyzed. Results We found that COL1A1 mRNA expression was significantly upregulated in premalignant and malignant tissues than in normal tissues, whereas COL1A2 mRNA expression was significantly higher in malignant tissues than in premalignant and normal tissues. Moreover, COL1A1 expression was unrelated to clinicopathological parameters, while COL1A2 expression was positively related to tumor size and depth of invasion. Besides, higher COL1A1 and COL1A2 expression levels were related to lower overall survival. Conclusions We find that COL1A1 might have its potential as a monitoring factor to screen early gastric cancer, and COL1A1 and COL1A2 might predict poor clinical outcomes in gastric cancer patients.